15c+7=11c+35

Simple and best practice solution for 15c+7=11c+35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15c+7=11c+35 equation:


Simplifying
15c + 7 = 11c + 35

Reorder the terms:
7 + 15c = 11c + 35

Reorder the terms:
7 + 15c = 35 + 11c

Solving
7 + 15c = 35 + 11c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-11c' to each side of the equation.
7 + 15c + -11c = 35 + 11c + -11c

Combine like terms: 15c + -11c = 4c
7 + 4c = 35 + 11c + -11c

Combine like terms: 11c + -11c = 0
7 + 4c = 35 + 0
7 + 4c = 35

Add '-7' to each side of the equation.
7 + -7 + 4c = 35 + -7

Combine like terms: 7 + -7 = 0
0 + 4c = 35 + -7
4c = 35 + -7

Combine like terms: 35 + -7 = 28
4c = 28

Divide each side by '4'.
c = 7

Simplifying
c = 7

See similar equations:

| -5(-4+9x)= | | 7r=2(4r-9) | | (9y/14)/(6/14) | | -7(x+1)+7(7+x)= | | 2x+(2x-8)=72 | | X-7/8=-7/12 | | X(-2x+5)=33 | | 6m-3=1/3m | | -15=(3n/5) | | X-7/8=7/12 | | 48x-4=13x+6 | | -7+6p=-97 | | X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] | | 4-5a=4(1+8a) | | 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 | | X-6-20=142 | | 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 |

Equations solver categories